Design and Simulation of Ornithopter based on Four-bar Mechanism - Zhao Zhifang; Qi Mingsi; Feng Jingkai; Zhang Wei; Wang Junyuan; Zhang Jiping (Jixie chuandong, 2017)
In order to study the twin joint structure of bird wings,a flapping wing structure based on four-bar mechanism is designed based on the principle of bionics. The brushless motor driving two stage reducer,provides input for four-bar mechanism. The robot has a function of the periodic flapping motion,the frequency change and size of the attitude angle adjustment. According to the range of bird joint angular motion,the output angle of the robot linkage mechanism is determined so that it can move within the expected range. The model is established by MATLAB/SimMechanics,and the four-bar mechanism of the robot is simulated and integrated into the iSIGHT software to optimize the parameters and obtain the design variable value similar to the expected trajectory. The results show that the ornithopter scheme design based on the design of the four-link mechanism is feasible,and the frequency is controllable. In addition,the optimized simulation curve can well approach the given task trajectory. The design method proposed in this paper has the characteristics of fast and efficient,and the result is intuitively visible,which provides a feasible scheme for parameter setting and optimization of other mechanical structure.